Evaluation of the Behaviour of Reinforced Concrete Curved in-Plane Beams (Iraqi Journal of Civil Engineering, 2010)
AbstractA full three dimensional finite element computational model is constructed for nonlinear analysis of reinforced concrete curved beams. This model was presented utilizing computer program ANSYS (Version 11), which is capable of an efficient analysis of the response at different load levels including ultimate loads.This work deals with the structural analysis of concrete curved beams behaviour subjected to two concentrated loads. Concrete curved beams are widely used in building and bridge constructions. Some of the available experimental tests on reinforced concrete curved beams are theoretically analyzed. This covers load-deflection relationships, crack pattern and propagation of crack at different stages of load and ultimate load capacity. The reliability of the model is demonstrated by comparison with available experimental results and alternative numerical analyses which shows 4 – 8 % difference.